The Impact of Cross-Cultural Adjustment and Intercultural Sensitivity on Intergroup Bias in Migrant Students - Yanies Novira Soedarmadi; Tabah Aris Nurjaman (UIN Sunan Kalijaga, 2026)
Issues faced by migrant students, such as misperceptions, prejudice, and discrimination, can lead to intercultural conflicts and physical violence that warrant further investigation. This study aimed to examine the contributions of cross-cultural adjustment and intercultural sensitivity to intergroup bias among migrant students in the Special Region of Yogyakarta. Participants included 96 migrant students residing outside the Special Region of Yogyakarta with diverse ethnic cultural backgrounds, selected via purposive sampling. The measurement instruments comprised the Cross-Cultural Adjustment Scale, the Intercultural Sensitivity Scale, and the Intergroup Bias Scale. Data were analyzed using multiple regression. Results indicated a significant effect of cross-cultural adjustment and intercultural sensitivity on intergroup bias among migrant students (F = 40.404; df = 2; p < .001). The combined contribution of cross-cultural adjustment and intercultural sensitivity to the reduction of intergroup bias was 46.5%. Beberapa isu yang dihadapi mahasiswa perantau seperti kesalahan persepsi, prasangka, dan diskriminasi dapat menyebabkan munculnya konflik antarbudaya dan kekerasan fisik yang perlu untuk dikaji lebih jauh. Penelitian ini bertujuan untuk mengetahui bagaimana kontribusi penyesuaian lintas budaya dan sensitivitas antarbudaya terhadap intergroup bias pada mahasiswa perantau di Daerah Istimewa Yogyakarta. Subjek penelitian terdiri dari 96 orang mahasiswa perantau yang berdomisili di luar Daerah Istimewa Yogyakarta dengan latar belakang suku budaya berbeda, yang diperoleh melalui teknik purposive sampling. Instrumen penelitian yang digunakan dalam pengukuran adalah Skala Penyesuaian Lintas Budaya, Skala Sensitivitas Antarbudaya dan Skala Intergroup Bias. Analisis data menggunakan regresi berganda. Hasil penelitian menunjukkan pengaruh negatif variabel penyesuaian lintas budaya dan sensitivitas antar budaya terhadap intergroup bias pada mahasiswa perantau (F = 40.404; df = 2; p < .001). Kontribusi penyesuaian lintas budaya bersama dengan sensitivitas antarbudaya terhadap penurunan intergroup bias adalah sebesar 46,5%.